Syndromes of abnormal muscular activity: overlap between continuous muscle fibre activity and the stiff man syndrome. Issue 3 (March 1983) - Valli, G; Barbieri, S; Cappa, S; Pellegrini, G; Scarlato, G
Abstract : Four patients with muscular pain, fasciculations, contractures or cramps are presented. Evidence of peripheral nerve involvement was revealed by electromyography and nerve conduction studies. Muscle biopsy showed mild signs of denervation and reinnervation and, at electron microscopy, dilatations of terminal cisternae were found. All patients showed a remarkable improvement after therapy with diphenylhydantoin or carbamazepine. These clinical, neurophysiological and morphological data underline the role of peripheral nerve pathology in various syndromes of abnormal continuous muscular activity.